Sequential parametric optimization of methane production from different sources of forest raw material - Matsakas, Leonidas; Rova, Ulrika; Christakopoulos, Paul (Frontiers in Microbiology, 2015)
The increase in environmental problems and the shortage of fossil fuels have led to the need for action in the development of sustainable and renewable fuels. Methane is produced through anaerobic digestion of organic materials and is a biofuel with very promising characteristics. The success in using methane as a biofuel has resulted in the operation of several commercial-scale plants and the need to exploit novel materials to be used. Forest biomass can serve as an excellent candidate for use as raw material for anaerobic digestion. During this work, both hardwood and softwood species―which are representative of the forests of Sweden―were used for the production of methane. Initially, when untreated forest materials were used for the anaerobic digestion, the yields obtained were very low, even with the addition of enzymes, reaching a maximum of only 40 mL CH4/g VS when birch was used. When hydrothermal pretreatment was applied, the enzymatic digestibility improved up to 6.7 times relative to that without pretreatment, and the yield of methane reached up to 254 mL CH4/g VS. Then the effect of chemical/enzymatic detoxification was examined, where laccase treatment improved the methane yield from the more harshly pretreated materials while it had no effect on the more mildly pretreated material. Finally, addition of cellulolytic enzymes during the digestion improved the methane yields from spruce and pine, whereas for birch separate saccharification was more beneficial. To achieve high yields in spruce 30 FPU/g was necessary, whereas 15 FPU/g was enough when pine and birch were used. During this work, the highest methane yields obtained from pine and birch were 179.9 mL CH4/g VS and 304.8 mL CH4/g VS, respectively. For mildly and severely pretreated spruce, the methane yields reached 259.4 mL CH4/g VS and 276.3 mL CH4/g VS, respectively. We have shown that forest material can serve as raw material for efficient production of methane. The initially low yields from the untreated materials were significantly improved by the introduction of a hydrothermal pretreatment. Moreover, enzymatic detoxification was beneficial, but mainly for severely pretreated materials. Finally, enzymatic saccharification increased the methane yields even further.